Violencias basadas en género: la otra tragedia de Colombia Planteamientos académicos - Betancur Arias, Juan Diego (Universidad Católica Luis Amigó, 2022)
This book, a product of academic and discursive activity, develops five chapters of scientific dissemination in which it presents an interdisciplinary analysis of the phenomena that extend in gender violence against women. The first chapter deals with the factual circumstances for the imputation of femicide in Colombia; the second chapter constructs a clinical psychological approach to the aggressor; the third chapter establishes an analysis of femicide from the logics of evolutionary and developmental psychology; the fourth chapter refers to the warp and woof of the brand of violence against women; the fifth chapter analyzes the cultural, social and educational elements of hegemonic machismo as a precipitating, maintaining and creating factor of violence against women. This publication seeks to contribute to the social, academic and scientific expansion of gender-based violence as another of Colombia's most atrocious tragedies that require a refined view on the part of divergent and critically grounded thinking.